Kajian Sosio-Biologi Minuman Baram Masyarakat Dayak Wilayah Katingan Kalimantan Tengah - Rita Rahmaniati; Supramono Supramono (Anterior Jurnal, 2014)
The purposes of this research are for 1) To describe a perception about “Baram” in Dayak Ethnic in Katingan, Central Kalimantan. 2) To analyze the content of alcohol in “Baram”. 3) To analyze the content of microorganism in “Baram”. 4) To exam the Organoleptic in “Baram” in Dayak Ethnic in Katingan, Central Kalimantan. The result of this research showed that 1) People perception in Dayak Ethnic in Katingan, Central Kalimantan toward “Baram” showed that almost all of the people don’t know the content of alcohol in “Baram” so there is a tendency to the people to still use “Baram” as a special drink for special ceremony because they have not enough knowledge about the positive and negative effect from “Baram”. 2) The content of alcohol that consists of “Baram” has a high category of 5,6% ethanol, relatively more high rather than “Tuak” only 4%: 3) The role of microorganism in Baram fermentation process are Saccharomyces cerevisiae and Saccharomyces bayanus and Aspergillus onzae; 4) Based on the result of Organoleptic examination of “Baram” in Dayak Ethnic in Katingan, Central Kalimantan we can conclude that the people like “Baram” because it has special taste and smell.